Design the circuit to generate square wave for electroporation technique - Syamiza, Ghazali (2018)
In daily life, fossil fuels is a primary energy sources but it cannot hold for a lifetime. This is because, every day, people use the fossil fuels to generate energy and cause the decrease of the main source of the energy in the future. Besides, burning the fossil fuels also can give bad effect to greenhouse which usually come from transportation and industry. It can cause global warming which can lead to climate changes. Therefore, our research aimed how to produce lipid that make biodiesel in a short time, with less energy input and eco-friendly. To do this we used electroporation process, where we employed a high voltage for shorter time on yeast cell to disrupt them. Our reactor took around 5 minutes to disrupt the cell wall for escaping intracellular lipid which could be used for biodiesel synthesis. The developed circuit can employ 1KHz to 8KHz. . The circuit can generate square wave output for electroporation process and can control the frequency and voltage as well.